PENENTUAN PERCEPATAN GRAVITASI BUMI BERBANTUAN MEDIA PHET DENGAN TEKNIK RATA-RATA BERBOBOT - Saumarachmawati, Putri Ani; Toifur, Moh (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The value of gravitational acceleration (g) varies across different locations depending on the distance from the surface to the Earth's center of mass. Additionally, the value of ggg is influenced by the data processing method employed. This study aims to determine the Earth's gravitational acceleration in the Banten region using a pendulum assisted by the Phet pendulum-lab simulation. The experiment was conducted using two methods: the average technique and the weighted average technique. For the average technique, the period was measured 10 times for a string length of 80 cm. For the weighted average technique, the period of the pendulum swing was measured at varying string lengths from 80 to 100 cm, with five variations, each measured 10 times. The results of the study showed that the gravitational acceleration determined using the average technique was 9.72 ± 0.28 m/s², while the weighted average technique yielded 9.78 ± 0.08 m/s². With the reference value of gravitational acceleration being 9.80 m/s², the weighted average technique successfully corrected the relative error from 0.82% to none. Moreover, the determination of gravitational acceleration using the weighted average technique produced more accurate results compared to the average technique. This study also confirms that the PhET simulation is an effective and reliable tool for measuring gravitational acceleration, particularly when physical experimental conditions are less than ideal. The weighted average technique significantly contributes to improving measurement precision, making it valuable for both physics research and education